The performance of minimum variance portfolios in the Croatian tourism sector - Suzana Baresa; Sinisa Bogdan; Zoran Ivanovic (UTMS Journal of Economics, 2018)
Croatian economy is largely dependent on tourism, the direct contribution of travel and tourism to GDP is 10.7%, while total contribution amounts 24.7%, tourism has great impact on employment also. Since tourism is one of the most important sectors for Croatian economy, the aim of this research was to analyze stock liquidity in Zagreb stock exchange and to construct efficient frontier which includes only tourism stocks. Level of liquidity for the Croatian market is generally very low, so only certain stocks which met liquidity criterium were used in this research. Currently there are 31 stocks listed on the Croatian capital market in the tourism sector, and this sector is one of the largest on the Zagreb stock exchange. Purpose of this research was to find out which performance have minimum variance portfolios in Croatian tourism sector, and to measure market risk in a portfolio using value-at-risk methodology. In this research two approaches of measuring value-at-risk methodology have been used: historical and conditional, results were compared with stock market index Crobex and explained.
Keywords: G11; L83; 330; Portfolio theory; illiquidity; stocks; efficient frontier; value at risk